Patient Experience of Lichen Planus: A Qualitative Exploration of Signs, Symptoms, and Health-Related Quality of Life Impacts - Aoife Mahon-Smith; Molly Clifford; Anjali Batish; Rosie Sharp; Charlotte Panter; Christel Naujoks; Eva Schruf; Nicolò Compagno; Santiago G. Moreno (Adis, Springer Healthcare, 2023)
Abstract Introduction Lichen planus (LP) is an inflammatory skin disorder that can present in various forms across the body, including lesions on the skin (cutaneous LP [CLP]), scalp (lichen planopilaris [LPP]), and mucosal regions (mucosal LP [MLP]). Qualitative exploration of the patient experience of LP, notably symptoms and impacts on health-related quality of life (HRQoL), is limited. A scarcity of research was also identified relating to emotional wellbeing impacts of CLP patients. Two qualitative studies were conducted with LP patients to address these gaps. Methods Study 1 consisted of exit interviews conducted with a subset of adult patients with MLP (n = 5), CLP (n = 4), and LPP (n = 4) enrolled in an LP clinical study in the United States (US) to explore the patient experience. Study 2 consisted of independent qualitative interviews conducted with adult CLP patients (n = 13) from the US and Germany to further explore impacts on emotional wellbeing. Results Exit interviews found that itch , pain, and skin lesions were most frequently reported as signs/symptoms of LP. Itch and skin lesions were experienced across all LP subtypes, while pain was only reported by CLP and MLP patients. These signs/symptoms impacted HRQoL including emotional wellbeing (frustration, embarrassment), daily activities (oral hygiene, clothing options), social functioning (intimacy, social activities), and physical functioning (chewing/swallowing, opening/moving mouth). Impacts on activities of daily living (ADL) and physical functioning were mostly experienced by MLP patients. Independent qualitative interviews, which further explored impacts of CLP on patients' emotional wellbeing, identified frustration, worry, sadness, embarrassment, and depression as the most frequently experienced. Conclusion The findings contribute to the literature by providing qualitative insights into signs/symptoms and HRQoL impacts of LP, from the adult patient perspective. The findings also highlight the importance of considering assessment of HRQoL impacts in future clinical LP research, particularly impacts on emotional wellbeing when selecting instruments for assessment of HRQoL in the CLP population. Trial Registration NCT04300296.